The nexus of transformational leadership, compensation and knowledge management towards employee performance: mediation role of work motivation - Baskoro, Bimmo Dwi; Widjaja, Bernard Tirto; Sudarmadji, Sudarmadji (Management and Entrepreneurship: Trends of Development, 2021)
This research aimed to analyze the nexus of transformational leadership (TL), compensation (CM), and knowledge management (KM) on employee performance (EP) through work motivation (WM) on engineering consulting companies in Capital Region of Jakarta. This was a causality research which used survey approach. The analysis unit of this research was some engineering companies represented by the experts of construction planners. They had high qualification and they were the members of National Association of Indonesian Consultant (Inkindo) in Capital Region of Jakarta, Indonesia. The target sample of this research was consulting company organizations represented by permanent experts or skilled manpower who worked in construction planning services. The data collection of this research was primary and secondary by using structural equation modeling with partial least squares method. The total respondent of this research was 106 who were the employees from selected engineering consulting companies in Capital Region of Jakarta. TL had a significant effect towards EP through work motivation. CM had a significant effect towards EP through WM. Lastly KM had a significant effect towards EP through WM. The importance of this research was taken from its context which was conducted in Capital Region of Jakarta, Indonesia. Moreover, this was one of initial efforts to indicate EP by considering TL, CM, and KM and to observe the use of EP for engineering consulting companies in Indonesia. The findings of this research could serve several inputs for organizations in developing the practices between WM dimension and KM expansion among consulting engineering companies in Capital Regional of Jakarta, Indonesia. JEL Classification: D23, J30.